Wound infections in adult patients after Berlin Heart EXCOR biventricular assist device implantation - Kremer, Jamila; El-Dor, Abbas; Rivinius, Rasmus; Schlegel, Philipp; Sommer, Wiebke; Warnecke, Gregor; Karck, Matthias; Ruhparwar, Arjang; Meyer, Anna L. (Life, 2022)
The Berlin Heart® EXCOR is a paracorporeal, pulsatile ventricular assist device used in patients of all age groups. However, adolescent and adult patients on EXCOR support are scarcely explored. Herein, we present a detailed description of infectious complications in this patient cohort. From 2006 to 2020, 58 patients received a biventricular assist device (BiVAD) at our institution and were included in this study. Postoperative infections were assessed after BiVAD implantation and subsequent heart transplantation (HTx). A Berlin Heart® EXCOR BiVAD was implanted as a bridge to transplantation in 58 patients (12-64 years). Most patients were INTERMACS I, and their median age was 49 years. Wound infections (WI) specific to the ventricular assist device (VAD) occurred in 31 (53.4%) patients with a mean time of 113 ± 155 days after BiVAD implantation. HTx was performed in 30 (51.7%) patients and thereof 10 (33.3%) patients developed at least one WI post-HTx. The mean time of WI after HTx was 17 ± 14 days. In four cases, WIs were caused by the same pathogen as before HTx. According to our institutional BiVAD wound classification, the mean wound score was 3. The VAD-specific wound infections were manageable and did not increase mortality nor precluded HTx in Berlin Heart® EXCOR patients. No specific risk factors for VAD-specific wound infections could be identified.